Flora flower store: different deliveries to create an innovative service experience - Palacios-Chacon, Lorena A.; Ortiz Velasquez, Mauricio; Giraldo, Mario (Estudios de Administración, 2019)
FLORA Flower Shop was, in 2018, a flower shop located in the Riomar zone of Barranquilla, Colombia. During that same year Andrea Cabarcas Castro, its founder, was worried about the future growth of the company. She was thinking of strategies to improve the weaknesses she had detected and was clear that she should maintain FLORA’s differentiating factors. The delivery of the floral arrangements to the final consumer represented an opportunity for improvement since this was the time when detailed control of the FLORA service experience could be lost due to protocol breaches. This could affect the positive positioning of the brand, leading to a bad reaction by consumers in the post-purchase experience, resulting in a negative impact on financial results.It was October 2018 and Andrea had until December of that same year to decide. Her main objective was to maintain the growth of the company, without negative effects on the delivery service.